Palaearctic Abaristophora (Diptera: Phoridae): First female of A. arctophila Schmitz, 1927 and a new species from N. W. Russia - Pape, Thomas; Ulefors, Sven-Olof; Disney, R. Henry L. (Zootaxa, 2013)
Abaristophora arctophila Schmitz, 1927 is confirmed from Europe through a series of males and females collected in bo-real Sweden. The male of A. arctophila is documented and separated from A. sachalinensis Michailovskaya, 1988 and Abaristophora kolaensis Disney n. sp., which is described from a single male from N.W. Russia. A lectotype is designated for A. arctophila and the female is described for the first time.